Basketball Affects Bone Mineral Density Accrual in Boys More Than Swimming and Other Impact Sports: 9-mo Follow-Up - Agostinete, Ricardo R. [UNESP]; Lynch, Kyle R. [UNESP]; Gobbo, Luís A. [UNESP]; Lima, Manoel Carlos Spiguel [UNESP]; Ito, Igor H. [UNESP]; Luiz-de-Marco, Rafael [UNESP]; Rodrigues-Junior, Mario A. [UNESP]; Fernandes, Romulo A. [UNESP] (Elsevier, 2016)
The objective of this study was to analyze the effect of different sports on bone mineral density (BMD) accrual among male adolescents during a 9-mo follow-up. The sample was composed of 82 boys (control [n = 13], basketball [n = 14], karate [n = 9], soccer [n = 18], judo [n = 12], and swimming [n = 16]) who were followed up for 9 mo (from October 2013 to August 2014). BMD (gram per square centimeter) was assessed at baseline and follow-up using a dual-energy X-ray absorptiometry scanner, whereas somatic maturation was estimated through the use of the peak height velocity. Vitamin D consumption was assessed by questionnaire. After 9 mo of follow-up, all groups (including the control group) presented significant BMD accrual (overall sample: 4.5% in the whole body). On the other hand, the basketball group presented higher BMD accrual in the upper limbs (17.6%) than the control group (7.2%). A similar difference was observed in whole-body BMD (control group: 4.1% vs basketball group: 7.1%). The basketball group had significantly higher BMD gains than the control group and other sports groups.
Keywords: Adolescents; bone mass; impact sports; swimming